Diagnosis and management of trauma by penetrating foreign body in orbit: Case series - Lucena, Virgínia Raquel dos Santos (2021)
Introduction: Intraocular foreign bodies are the major cause of traumatic injuries in orbit, they have different characteristics, ranging from eyelid edema to cranial orbit trauma, they occur in severe and sometimes fatal sequelae. Objective: The objective of the present study is to present a series of cases of trauma by a penetrating foreign body in the eye socket associated with a literature review on the subject. Design: Retrospective case study. Methodology: Review according to the PRISMA statement, using the PubMed, Science Direct and SciELO databases, in addition to the case reports and retrospective analysis of 12 patients on different managements. Results: The mean age of the patients was 31.16 years, with 91.6% of the patients being male, the etiology in 50% of the cases of the wood material, in 41.7% it was by metal and in 8, 3 % of glass. Computed tomography was used in all cases obtained with effective results. In 58.3% of the cases, they occurred in the left orbit. Fifty percent of treated cases evolved without sequelae. Conclusion: Early diagnosis and immediate management of orbital lesions are essential for a positive prognosis, as well as adequate imaging tests. Computed tomography, magnetic resonance and computed tomography angiography are frequently used and effective imaging modalities.